Preparation and properties of butadiene-acrylonitrile-butylacrylate terpolymer - SHI Gong-chang, ZHONG Qi-lin, WANG Yong-feng, YANG Hai-long, ZHAO Zhi-chao (Hecheng xiangjiao gongye, 2023)
Butadiene-acrylonitrile-butylacrylate terpolymer (BNBR) was synthesized by emulsion polymerization method. The effects of amount of initiator, emulsifier and regulator of relative molecular weight on the emulsion polymerization rate were investigated. And the microstructure and dynamic mechanical properties were characterized. The results showed that the polymerization rate increased and the reaction induction period shortened with increasing polymerization temperature. The increasing amount of initiator and emulsifier could increase the reaction rate, while the change in the amount of relative molecular weight regulator had little effect on the reaction rate. The apparent activation energy of the BNBR was 27.97 kJ/mol, and the particle size distribution of BNBR latex was uniform. The glass transition temperature of BNBR was lower than that of nitrile rubber（NBR）with a difference of about 10 ℃. BNBR had better dynamic mechanical pro-perties at low temperature than NBR.